PENGARUH PENGALAMAN KERJA, ETIKA PROFESI, INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT INTERNAL - Welly Welly; Sumita Sumita; Yulian Sahri; Lis Djuniar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The formulation of the problem in this research is 1) How is the influence of work experience, professional ethics, independence and professionalism on the quality of internal audit simultaneously. 2) How is the effect of work experience on the quality of internal audit partially. 3) How is the influence of professional ethics on the quality of internal audit partially. 4) How is the effect of independence on the quality of internal audit partially. 5) How is the influence of professionalism on the quality of internal audit partially. The data used in this research is primary data. The sample in this study was addressed to auditors in the offices of state-owned enterprises (BUMN) in the Energy, Oil and Gas Sector, Manufacturing Sector, Food and Fertilizer Sector, Logistics Sector, Telecommunication and Media Sector in Palembang City. Data collection methods used in this study were interviews and questionnaires. The data analysis method in this research is quantitative analysis. The data analysis technique was assisted by the Software Statistical Program For Special Science (SPSS). The results of this study indicate that 1) simultaneously work experience, professional ethics, independence and professionalism have a significant effect on the quality of internal audit. 2) partially work experience has a significant effect on the quality of internal audit. 3) partially professional ethics has no significant effect on the quality of internal audit. 4) partially independence has no significant effect on the quality of internal audit. 5) partially professionalism has a significant effect on the quality of internal audit.